IMPLEMENTASI MODEL PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN KETRAMPILAN SOSIAL SISWA - Suryani, Nunuk (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Collaborative learning is a philosophy and lifestyle interaction that makes cooperation as an interaction structure. This structure is designed to facilitate achieve common goals collectively. In every situation, when several people are in a group, the collaboration was a way to deal with mutual respect and appreciate the capabilities and contributions of each member of the group. In it there is division of authority and revenue responsibilities among the group members to carry out the action of group. The main idea underlying the collaborative learning is a consensus built up through cooperation among group members as opposed to a competition which put the benefits of the individual. The collaborative learning practitioners utilize this philosophy in the classroom, in committee meetings, in various communities, in families and is widely as a way of living with and interacting with others. Collaborative learning needs to be applied in schools. Collaborative ways of learning is more moving or encourage students to a active and interactive as well as cooperation in completing academic tasks in the classroom. Thus, collaborative learning is fundamentally different from conventional-traditional approach has been done, the better, "direct-transfer, or" one-way transmission "model. In this case the student becomes the sole source of knowledge or skills. Learning view more collaborative learning process as, "learner-centered" and not,, "teacher-centered." Knowledge is seen as a social construct, facilitated through the interaction between peer groups, evaluation and cooperation. Therefore, the role of learning changed from the information transmitter (transferring knowledge), "the stage on the stage" to be a facilitator in self-learners to construct knowledge,, "the guide on the side". There are some benefits of collaborative and cooperative learning are implemented in schools in order to prepare future students. The benefits that we can take through the learning of collaboration and cooperation, namely in terms: a) the recognition of difference, 2) individual recognition, 3) sense of responsibility, 4) develop cooperation to achieve common goals, 5) mutual aid and understanding the problem- problems faced and find solutions, 6) gave a positive response to the other party, 7) development of common views in collaborative work, and 8) the existence of mutual dependence on one another.